Waqf on Infrastructure: How Far has been Researched? - Ririn Riani; Ahlis Fatoni (International Journal of Waqf, 2022)
One of the main objectives of waqf, which is called Tasbil al-Thamarat, is to make waqf assets useful and productive. Waqf properties must be developed using instruments that can provide good benefits for waqf. Profits from waqf assets must be used for the benefit of the welfare of Muslims. Waqf infrastructure is considered as the most effective way to ensure the expansion of waqf while at the same time providing distribution services to the general public. This bibliometric study maps research related to the development of Waqf and Infrastructure research trends published by leading journals from 2001 to 2021 which have been indexed by Scopus. Analysis is focused on trending keywords, authors and institutions. The data analyzed were 118 research publications. This study provides information for researchers who focus on research in the field of Islamic Philanthropy, especially waqf infrastructure instruments. In the end, this theme has the potential to continue to be developed.